2021
DOI: 10.1038/s41598-021-83519-z
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between auxin and gibberellin during stalk elongation in flowering Chinese cabbage

Abstract: Plant growth and development are tightly regulated by phytohormones. However, little is known about the interaction between auxin and gibberellin acid (GA) during flower stalk elongation and how it is directly related to organ formation. Therefore, the effects of indole acetic acid (IAA) and GA3 treatments and their interaction on flower stalk elongation in flowering Chinese cabbage were investigated. The growth of flowering Chinese cabbage is regulated by IAA and GA3, and the opposite results were observed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Cell cycle regulation of the shoot apical meristem affects stem elongation and thickening, and BcEXPA11 and BcXTH3 are the key factors responsible for cell expansion [ 44 , 45 ]. EXPA11 promotes the sliding of polymers such as cell wall cellulose and hemicellulose by reducing the viscosity of polysaccharides between cell walls and enabling cell wall expansion [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle regulation of the shoot apical meristem affects stem elongation and thickening, and BcEXPA11 and BcXTH3 are the key factors responsible for cell expansion [ 44 , 45 ]. EXPA11 promotes the sliding of polymers such as cell wall cellulose and hemicellulose by reducing the viscosity of polysaccharides between cell walls and enabling cell wall expansion [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stem elongation, thickening, and flowering are key characteristics of flowering Chinese cabbage stem development. Factors that affect the timing of the bolting and flowering of flowering Chinese cabbage include temperature and plant hormones [3][4][5]. Low temperature and exogenous gibberellin A3 (GA 3 ) treatment advance bolting time, stem elongation, and flowering time.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several recent studies have shown reciprocal interactions between the two hormones where cytokinin inhibits the production GA and promotes its deactivation and GA inhibits cytokinin responses [11]. In flowering Chinese cabbage, endogenous plant hormones activities are closely relayed to bolting [3,24]. Three-true-leaf spraying of cytokinin promoted the thickening growth of diameter and inhibited stem elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Three cyclin-related genes-CDKB2-1, CDKB2-2 and CYCD3-1-and one cell expansion gene-EXPA11-were selected to analyze the expression characteristics of these genes at bud emergence stage after different hormones. EXPA11 functions as a key factor responsible for cell expansion by promoting the sliding of polymers such as cell wall cellulose and hemicellulose [24,25]. In addition, cell cycle regulation affects stem elongation and thickening in the shoot meristem [26].…”
Section: Qrt-pcr Analysis Of Bolting-related Genes Responded To Zt In...mentioning
confidence: 99%